2017
DOI: 10.3390/ijerph14060634
|View full text |Cite
|
Sign up to set email alerts
|

Providing a Clean Environment for Adolescents: Evaluation of the Tobacco Hazards Prevention Act in Taiwan

Abstract: Cigarette smoking not only damages the health of adolescents, but also contributes to air pollution. The Tobacco Hazards Prevention Act in Taiwan stipulates that cigarettes should not be sold to persons younger than 18 years. Therefore, schools should actively educate students and raise awareness of the Tobacco Hazards Prevention Act to reduce the level of damage to the health of adolescents and maintain good air quality. This study had two main goals: (1) to evaluate the stipulation that no person shall provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Smoking not only damages the health of adolescents but also contributes to the environment in which air pollution occurs. The Tobacco Hazard Prevention Act in Taiwan stipulates that cigarettes may not be sold to people under the age of 18 [52]. This is almost similar to the research that showed that the cigarette filter is the most global and one of the main sources of marine pollution.…”
Section: Discussionsupporting
confidence: 54%
“…Smoking not only damages the health of adolescents but also contributes to the environment in which air pollution occurs. The Tobacco Hazard Prevention Act in Taiwan stipulates that cigarettes may not be sold to people under the age of 18 [52]. This is almost similar to the research that showed that the cigarette filter is the most global and one of the main sources of marine pollution.…”
Section: Discussionsupporting
confidence: 54%
“…The concerns of Taiwanese people about e-cigarettes ( t 5 ) could be attributed to the emerging trend of adopting e-cigarettes by teenagers. After enacting the Tobacco Hazards Prevention Act [ 90 ], the Taiwanese government now prohibits smoking in all workplaces and other public places, and requires warnings to appear prominently on cigarette packages that encourage people to stop smoking. However, the diffusion rates of e-cigarettes from middle school to high school students have increased rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research on adolescent smoking mainly focuses on medical health, smoking behaviors and attitudes, the impact of smoking on adolescents, and the complications of adolescent smoking [ 9 ]. Hanewinkel et al discovered the peculiarities of the relationship between tobacco marketing and youth smoking and verified that the exposure of adolescents to cigarette advertisements under high exposure is related to the occurrence of adolescent smoking [ 10 ].…”
Section: Introductionmentioning
confidence: 99%